SIFAT FISIK DAN MEKANIK BIOPLASTIK DARI PATI KULIT PISANG AMBON (Musa paradisiacal) DENGAN PLASTICIZER SORBITOL - Endo Pebri Dani Putra (Agroindustrial Technology Journal, 2022)
Bioplastic is one solution to the large amount of plastic waste that is a problem for the environment because it is difficult to degrade. This study aims to characterize the bioplastic film of ambon banana peel starch and to determine the best ambon peel starch concentration. Observations on the resulting bioplastic products are physical properties and mechanical properties. Physical properties tests include thickness, density, water absorption and mechanical properties including tensile strength, percent elongation, young's modulus. The results showed that differences in starch concentration affected the thickness, density, water absorption, tensile strength, elongation and young's modulus. The best treatment based on the mechanical properties of bioplastics was the addition of 1 g of Ambon banana peel starch.